BUILDING A SUSTAINABLE GENERATION AS AN IMPACT OF CHARACTER EDUCATION IN EDUCATION AT SMPN 4 BANJARMASIN - Syaharuddin, Syaharuddin; Hasanah, Hasanah; Ilhami, M. Ridha; Syarifuddin, Syarifuddin; Triyono, Sigit (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
This study uses a case study design with a qualitative approach to gain an in-depth understanding of character education practices and their impact on sustainability at SMPN 4 Banajarmasin. This article discusses how character education can shape a sustainable generation and contribute to social and environmental sustainability. This study aims to explore how character education can influence the formation of a sustainable generation in the context of education for sustainability. A sustainable generation with character education forms a generation that has the noble values, morals, and ethics needed for sustainability, improving the quality of life by developing the skills needed to live sustainably, such as problem solving and other values, and positive social change, where students become good citizens and contribute to the progress of society.